Local Culinary Online Marketing Education in Pulotondo Village Tulungagung - Fatimah, Annisa; Sisdianto, Ersi; Noor, Nur Fariha binti Mohd (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
This PKM was carried out in an effort to provide knowledge sharing related to local culinary online marketing education in Pulotondo Village, Ngunut – Tulungagung Regency. Village existence must be taken a serious attention from the government through related policies. One of them is by empowering the economy carried out by official institutions for community economic activities, namely BUMDes . BUMDes manages village economic assets and resources in the context of empowering the village community's economy so that BUMDes directly participates in managing the economy in the village. One of the business fields that BUMDes can choose is a joint venture with the community. Therefore BUMDes business marketing education with various trainings that can increase the village's economic income. The initial step for educating the BUMDes Management Team as a contributor to strengthening the community's economy is to provide information, knowledge and skills, which must be carried out in multi-aspects, both from the community, social, cultural aspects, government policies and marketing potential for them. Growing entrepreneurial ideas, planning strategies to marketing continues to evolve into the needs of today's society. The PKM activity program is planned to be implemented has been coordinated with the BUMDes Management Team for Pulotondo Village, Kec . Ngunut – Kab . Tulungagung which will host the PKM activities by inviting all parties related to the PKM program. The presence of lecturers and students who are also entrepreneurial practitioners is expected to provide enlightenment and new knowledge which is quite meaningful for all participants.